Pengaruh Pengelolaan Keuangan Daerah, Akuntabilitas dan Transparansi Terhadap Kinerja Keuangan Pemerintah Daerah Di BPKAD Pemerintah Kota Tanjungpinang - Astuti, Henny Puji; Ilham, Muh.; Madjid, Udaya (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
This study aims to analyse and describe how much influence regional financial management, accountability and transparency have on the financial performance of the Tanjungpinang City local government. The research method used with a quantitative approach and associative design. The population in this study were civil servants/ASN employees who worked at BPKAD Tanjungpinang City Government as many as 42 people. As a comparison material, the measuring instrument was also distributed at Bappelitbang Tanjungpinang City Government with 51 employees. Thus the total population is 93 people. The sampling technique used is saturated sampling so that 93 respondents are obtained. The data analysis technique used in this research is path analysis. Based on the results of the analysis, it can be concluded that the significant effect partially or simultaneously of regional financial management, accountability and transparency on the financial performance of the Tanjungpinang City local government is 75.0% while the remaining 25.0% is influenced by other variables outside the research model.